Dynamic capabilities and performance: A supply chain perspective - Haris Aslam; Tashfeen M. Azhar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Ever changing market environment in terms of technology and competitive situation requires firms to continuously reconfigure their resource configurations. Based on the dynamic capabilities view of the firm, we propose the dynamic capabilities relevant in the context of supply chains. We conceptualize dynamic capabilities of a firm as consisting of multiple levels. Capabilities at the highest level affect the formation of first order dynamic supply chain capabilities. Furthermore, first order capabilities modify the operational capabilities. We propose constructs for second and first order dynamic supply chain capabilities. Performance implications of dynamic supply chain capabilities have also been empirically tested based on data from 275 managers from Pakistani manufacturing industry. The results show a support for the assertions by dynamic capability theorists.
Keywords: 330; dynamic supply chain capabilities; dynamic capabilities; operational capabilities; supply chain performance; structural equation modelling